"Closing in" on open spaces open space development of residential subdivision projects in the National Capital Region, Philippines - Datiles, Romeo R. (College of Architecture, University of the Philippines Diliman, 2010)
For over a number of decades, the rules and standard provisions of Presidential Decree 957 (PD 957) continue to regulate private housing development in the Philippines. These rules set the maximum allowable saleable areas at 70% of the total subdivision project area while the remaining 30%, is for non-saleable portions allocated for parks, playgrounds, and community facilities, called open spaces, and circulation system such as roads, alleys, among others. This study looked at how major housing firms in the National Capital Region (NCR) of the Philippines comply with open space requirements in the design and planning of residential subdivisions. A comparative study of 6 housing projects developed by major players in housing industry was done to investigate the patterns of development and the design approaches taken to allocate and distribute lot areas for open spaces. The findings show common and distinct characteristics, inclinations and trends in design and planning that were adopted in compliance to PD 957. These are seen in many ways by which design elements, distribution, scale, and hierarchy of the open space amenities were integrated into the development, thereby influencing planning allocations, design styles and marketing strategies in the production and distribution of housing.